Dampak Kepatuhan, Pemeriksaan, dan Penagihan Pajak Terhadap Penerimaan Pajak Penghasilan Badan - Shalihah Dwi Adini; Nera Marinda Machdar (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Taxes are the main source of income, they play a very crucial role in the life of the nation and state in the process of state infrastructure. Thus, the target of tax revenue should be achieved. Thus, it is important to conduct research to find components that can involve tax revenue. The purpose of this analysis is to see how the three components of taxpayer compliance, tax audits, and tax collection affect corporate income tax revenue. This study found that taxpayer compliance, tax audits, and tax collection have a meaningful and beneficial effect on corporate income tax revenue.